Implementasi Pemahaman Teologi Pernikahan Umat Hindu dan Kristen Di Pintubesi Bagi Kerukunan - Bilo, Dyulius Thomas; Hutahaean, Hasahatan (Jurnal Penelitian Agama Hindu, 2023)
In Pintubesi, Deliserdang Regency, the population consists that ethnic groups and the oldest religion, Hinduism. There, harmony and tolerance prevail among the believers. Christians and Hindus show mutual tolerance and cordiality. This phenomenon attracts researchers by studying the teachings of marriage between the two religions, which is believed to be one of the stimulants for creating harmonization and tolerance. The research was conducted qualitative method, which data was collected through in-depth interviews. The data were reduced and analyzed to meet the research objectives. The results showed that a good and correct understanding of the religious teachings in the field of marriage according to the religious teachings in its adherents the impetus for creating harmonization and tolerance in Pintubesi. Marriage a way to produce offspring, and Hinduism believed that the child sends the parents to the Creator after his death. Hinduism emphasizes equality for all, maintain tolerance and harmony religious’s. Valuing religious appeasement is requirement that's passed down through generations. Thus, common for society to accept relatives giving up their religious status to marry other religions. Similarly, Hindus of the Karo-Batak tribe, maintain closed harmonious relations with Karo people. Acceptance of other, as well as one's own, was taught an early age. Therefore, in both Hinduism and Christianity, the establishment of the family should be based on correct and strict dogmas before the household is established. Because through this segment it becomes the door for creating harmony and tolerance in the community.